Spectrophotometric Study of Dyes for Dye Sensitized Solar Cell (DSSC) - Moneer K. Mohsen (Journal of Global Pharma Technology, 2018)
This paper described the absorption spectra of some dyes (N719, N3, N749 and SQ2) were measurements as sentesizeed materials for dye- sensitized solar cell (DSSC). It was used commercially dyes namely N719, N3, N749 and SQ2. All samples prepared as solutions at different concentrations (10-4, 10-5, 10-6M), by using ethanol as a solvent, exclude SQ2 used methanol as a solvent. The samples were evaluated spectrophometricaly;UV-Vis spectra results proved that there were two peaks for (N719, N749, and N3) at (390and530nm), (430and626nm) and (390and540nm), respectively. While SQ2 dye showed one peak at 650nm. The calibration curves for these dyes involved were created, and the molar extinction coefficient was calculated for samples involved. The molar extinction coefficients for N719, N749, N3 and SQ2 were determined at previous peaks, and its values were(16406 M-1cm-1and 14135M-1cm-1),(10000 M-1 cm-1and 9329M-1 cm-1),(11974 M-1 cm-1and 10032 M-1cm-1)and(22384 M-1 cm- 1)1respectively,which it was found that SQ2 have high molar coefficients than previous dyes which was important in photon absorption and DSSC device photocurrent increase.Keywords: Dye, Absorption, Molar Extinction Coefficient, Dye sensitized solar Cell.